Standardising as governance: The case of credit rating agencies - Dieter Kerwer (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2001)
The global integration of financial markets has been accompanied by a transformation of their governance structures. Private intermediary organisations now play a more important role than in the past. A prominent example is provided by the commercial credit rating agencies that have established themselves as influential gatekeepers of the international credit market. A problem with this form of intermediation is that when there are errors rating agencies can do considerable damage to borrowers and investors alike. Still, it is very difficult to hold rating agencies accountable. This paper proposes comparing the activity of credit rating agencies with standard setting in order to explain this accountability gap. The argument is that the standards of credit-worthiness established by the rating agencies are difficult to challenge because they are based on neutral expertise, on the one hand, but are subject to mandatory enforcement by financial market regulation, on the other. The resulting compliance without complaints reduces the possibilities for learning. This perspective leads to a research agenda in which the preconditions and institutional remedies for accountability problems of global governance by private intermediary organisations can be comparatively explored.
Keywords: 330; Kreditwürdigkeit; Auskunftei; Standardisierung; Corporate Governance; Neue Institutionenökonomik; Theorie; Welt